Прикраси готського жіночого костюма VI—VII ст. (невідомі артефакти) - Хардаєв, В.М. (Археологія, 2016)
Уперше публікуються традиційні прикраси готського жіночого костюма доби раннього середньовіччя VI— VII ст. з колекції Національного музею історії України. Archaeological materials described in the article from the 6th and 7th centuries burials of women indicate that a peculiar for the Goths festive women’s dress was spread among the Germanic population of Tauria on the south coast, in the SouthWestern Crimea, as well as in Kerch in the Early Middle Age. Neither written, nor iconographic sources do not offer any concrete data on the Crimean Goths’ clothes of this period. It is possible to study their dress only after archaeological finds. The Museum’s collection of jewelry ornaments for the Gothic women’s dress, which were part of the funeral equipment in the Crimean necropoleis, contains pair silver gilt bow and radiate brooches of small and large sizes, huge silver belt buckles of different types, and also a series of gold hoop earrings with a polyhedron-shaped bead, gold pectoral crosses and silver bracelets. These decorative accessories can serve as chronological indicators for dating the graves and funeral objects. To define the types of jewelry ornaments the author uses the classification of items, which had been already developed in numerous scientific publications. Описываемые в статье археологические материалы из женских захоронений VI—VII вв. свидетельствуют о том, что в период раннего средневековья среди германского населения Таврии на южном побережье, в Юго-Западном Крыму, а также в Керчи получил распространение характерный для готов женский праздничный наряд. Конкретными данными об одежде крымских готов этого периода, как письменные, так и иконографические источники не располагают. Изучение костюма возможно только по археологическим находкам. Музейная коллекция украшений готского женского костюма из состава погребального инвентаря крымских некрополей включает парные серебряные позолоченные двущитковые и пальчатые малые и большие фибулы, разнотипные серебряные массивные поясные пряжки, а также серию золотых однобусинных серёжек, нательных крестиков и серебряных браслетов. Эти декоративные детали одежды могут служить хронологическими индикаторами для определения датировки могил и погребального инвентаря. Классификация изделий, разработанная в многочисленных научных публикациях, использована автором статьи для их типологизации.